Stroke occurring in patients with cognitive impairment or dementia - Solène Moulin; Didier Leys (Arquivos de Neuro-Psiquiatria)
ABSTRACT One in six patients admitted for stroke was previously demented. These patients have less access to appropriate stroke care, although little is known about their optimal management. Objective To determine how pre-stroke cognitive impairment can be detected, its mechanism, and influence on outcome and management. Methods Literature search. Results (i) A systematic approach with the Informant Questionnaire of Cognitive Decline in the Elderly is recommended; (ii) Pre-stroke cognitive impairment may be due to brain lesions of vascular, degenerative, or mixed origin; (iii) Patients with pre-stroke dementia, have worse outcomes, more seizures, delirium, and depression, and higher mortality rates; they often need to be institutionalised after their stroke; (iv) Although the safety profile of treatment is not as good as that of cognitively normal patients, the risk:benefit ratio is in favour of treating these patients like others. Conclusion Patients with cognitive impairment who develop a stroke have worse outcomes, but should be treated like others.